Simultaneous X‐Ray Diffraction and Tomography Operando Investigation of Aluminum/Graphite Batteries. (6th September 2020) - Elia, Giuseppe Antonio; Greco, Giorgia; Kamm, Paul Hans; García‐Moreno, Francisco; Raoux, Simone; Hahn, Robert
Abstract: Rechargeable graphite dual‐ion batteries are extremely appealing for grid‐level stationary storage of electricity, thanks to the low‐cost and high‐performance metrics, such as high‐power density, energy efficiency, long cycling life, and good energy density. An in‐depth understanding of the anion intercalation mechanism in graphite is fundamental for the design of highly efficient systems. In this work, a comparison is presented between pyrolytic (PG) and natural (NG) graphite as positive electrode materials in rechargeable aluminum batteries, employing an ionic liquid electrolyte. The two systems are characterized by operando synchrotron energy‐dispersive X‐ray diffraction and time‐resolved computed tomography simultaneously, establishing a powerful characterization methodology, which can also be applied more in general to carbon‐based energy‐related materials. A more in‐depth insight into the AlCl4 − /graphite intercalation mechanism is obtained, evidencing a mixed‐staged region in the initial phase and a two‐staged region in the second phase. Moreover, strain analysis suggests a correlation between the irreversibility of the PG electrode and the increase of the inhomogenous strain. Finally, the imaging analysis reveals the influence of graphite morphology in the electrode volume expansion upon cycling. Abstract : In‐depth insight into the AlCl4 − /graphite intercalation mechanism is obtained by operando synchrotron energy‐dispersive X‐ray diffraction and time‐resolved computed tomography simultaneously, establishing a powerful characterization methodology, which can also be applied more in general to battery‐related materials.